Mapping regional energy interests for S3P-Energy - Jiménez-Navarro, Juan-Pablo; Uihlein, Andreas (My University, 2016)
Mapping energy priorities under the framework of the smart specialisation concept may help policy makers to define actions plans as well as maximize the impact of available resources. This report identifies groups of regions and countries with common energy technology interests based on a set of technologies included in the Strategic Energy Technology Plan (SET-Plan) of the European Union. In order to carry out the mapping, the tool EYE@RIS3 has been used and more precisely the description provided by each territorial unit and collected by this tool. The methodology proposed to develop the mapping analyses aims to avoid an individual analysis of every single regional or national smart specialisation strategy. However, the approach proposed could lead to overlapping in terms of semantic interferences, an issue that has also been analysed in this report. Once the groups of regions/countries have been defined, potential similarities have been assessed based on socio-economic indicators. Finally, the level of alignment between regional and national levels has been studied. The findings of this report establish the basis to carry out a deeper analysis focused on a specific energy technology and with a reduced number of regions.
Política de acceso abierto del editor: https://data.jrc.ec.europa.eu/licence/com_reuse
Keywords: Energía - Consumo; Smart specialisation; Regional energy interests; EYE@RIS3; SET-Plan